Azathioprine in ulcerative colitis: final report on controlled therapeutic trial. - Jewell, D; Truelove, S (1974)
Eighty patients, all of whom were suffering from a frank clinical attack of ulcerative colitis, were admitted to the trial. The attack was treated with a standard course of corticosteroids and the patients were immediately placed on treatment with either azathioprine in a dose of 2.5 mg/kg body weight or dummy tablets. The trial tablets were continued for one year while the patients were maintained under regular clinical, sigmoidoscopic, histological, haematological, and biochemical surveillance. If a patient relapsed during such maintenance treatment he or she was treated with a further course of corticosteroids without interrupting maintenance treatment.In the treatment of an actual attack of ulcerative colitis the results in the attacks which brought the 80 patients into the trial show that no benefit came from the addition of azathioprine to a standard course of corticosteroid therapy.Patients admitted in their first attack of ulcerative colitis showed no benefit from the one-year maintenance treatment with azathioprine, the benefits of which were confined to patients admitted in a relapse of established disease. Even in these the difference between the treated group and the control group failed to reach statistical significance, but the difference was big enough to suggest that there is a prima facie case for regarding azathioprine as of some benefit in this group of patients.